2008
DOI: 10.1002/srin.200806154
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Lean Duplex Stainless Steel

Abstract: The classic series of duplex stainless steels shows very high corrosion resistance and can be used for very demanding applications. A new lean duplex steel, LDX 2101® (EN 1.4162, UNS S32101), has been developed with corrosion resistance on a par with standard austenitic grades. Application areas include: structural components, chemical industry, tanks and containers. The steel was designed to have equal amounts of ferrite and austenite in annealed condition and with an austenite that is stable against strain‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 6 publications
3
32
0
2
Order By: Relevance
“…6) Zhang 14) studied the effect of ageing on precipitation and impact energy of LDX 2101 and found that the most sensitive embrittlement temperature was about 700°C, and formation of nitrides was the main reason for the decrease of impact energy. Similar results were obtained by Charles 15) and Liljas, 16) indicating that nitride precipitation severely impaired the corrosion resistance and the toughness of the DSSs. Despite these studies on the precipitation in LDX 2101, [14][15][16] the microstructure evolution and mechanical properties have not been thoroughly clarified and still need to be further investigated.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…6) Zhang 14) studied the effect of ageing on precipitation and impact energy of LDX 2101 and found that the most sensitive embrittlement temperature was about 700°C, and formation of nitrides was the main reason for the decrease of impact energy. Similar results were obtained by Charles 15) and Liljas, 16) indicating that nitride precipitation severely impaired the corrosion resistance and the toughness of the DSSs. Despite these studies on the precipitation in LDX 2101, [14][15][16] the microstructure evolution and mechanical properties have not been thoroughly clarified and still need to be further investigated.…”
Section: Introductionsupporting
confidence: 83%
“…Also, high nitrogen content in LDX 2101 could retard or even prevent the formation of s-phase. 16,21) Therefore, increase of N content and decrease of Cr and Mo contents can lead to the absence of s-phase formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Recently, DSS were mainly classified into four types: hyper, super, standard, and lean type depending on the corrosion-resistant level. 5) Low-alloy steels called lean DSS such as inexpensive Type 32101 with a low Ni and Mo content are balanced by having increased N and Mn contents.…”
Section: Introductionmentioning
confidence: 99%
“…DSS alloys display better mechanical properties than single phase stainless steel alloys mainly because of the interaction between the phases [1]. Lean Duplex Stainless Steel 2101 (LDSS 2101) is a relatively new grade, lower cost DSS introduced by Outokumpo® in 2002 [2,3]. Lowering the cost was achieved by replacing expensive element alloys (nickel, molybdenum and chromium) with alternative cheaper elements [3]; LDSS 2101 has about 1.5% nickel compared to 5.5% and 12% of nickel in DSS 2205 and 316 austenite stainless steel, respectively [4].…”
Section: Introductionmentioning
confidence: 99%